Internalization of Religious Values in Child Parenting in the Digital Era: A Perspective from Tafsir Al-Mishbah - Mochammad Sidqi Awaliya Rahman (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study examines the construction of religious values in child parenting in the digital era through the development of an Islamic Digital Parenting model based on Tafsir al-Mishbah and Albert Bandura’s modeling theory. The study is motivated by the increasing challenges of digital parenting, which are not merely related to controlling children’s use of technology, but also to the internalization of religious values in children. This research employed a qualitative approach using a library research method and a thematic Qur’anic interpretation (tafsir maudhu’i) approach. The material objects of the study include Q.S. Al-Ahzab [33]:21, Q.S. Luqman [31]:13–16, and Q.S. Yunus [10]:99 as interpreted in Tafsir al-Mishbah by M. Quraish Shihab, while the formal object of the study is Albert Bandura’s modeling theory. Data were collected through documentation studies and analyzed using qualitative content analysis through the stages of data reduction, thematic categorization, interpretation, and conceptual synthesis. The findings reveal that Q.S. Al-Ahzab [33]:21 represents the value of exemplary conduct, Q.S. Luqman [31]:13–16 emphasizes tauhid and moral education, and Q.S. Yunus [10]:99 highlights responsible freedom of attitude. These three values are integrated with the stages of modeling, retention, reproduction, and motivation in Bandura’s theory, thereby forming an Islamic Digital Parenting framework that emphasizes parental role modeling, the strengthening of moral awareness, and the development of children’s responsibility in digital spaces. This study concludes that Islamic digital parenting positions technology as a medium for the internalization of religious values through exemplification, dialogue, and the cultivation of children’s spiritual awareness.